A Cross Sectional Study of Deaths Due to Poisoning: Autopsied at a Tertiary Care Centre: Davangere (Medico Legal Update, 2020)
Poisoning is an important health problem in every country of the world. Occupational exposure to industrialchemicals and pesticides, accidental or intentional exposure to household and pharmaceutical products andpoisoning due to venomous animals, Toxic plants and food contamination, all contribute to morbidity andmortality. Poison is a substance that being soluble in the blood either destroys life or impairs seriously thefunctions of one or more organs of the body. Poison can be defined as, a substance (solid, liquid or gas) whichif introduced in a living body or brought in contact with any part thereof will produced ill health or death byits constitutional or local effects or both.1 Due to rapid development in the field of science and technologyand vast growth in the industrial and agricultural sector, the poisoning is spreading like a wild fire. Poisoningis a medical emergency and the patients are invariably admitted to the hospital through emergency services.The poisoning may be suicidal, accidental or homicidal. With this background, the present study has beencarried out to determine the profile of poisoning cases, autopsied at SSIMS & RC, Davangere, Karnataka.The study revealed that victims of rural population (68.9%) are highest among the habitation, followed byurban population. Most of the victims are married people (63.9%). Most of the victims were educated withmatriculation (62.3%). Most of the poisoning cases are seen in Hindu religion (91.8%). Most of the caseswere seen in winter season (42.6%) and in most of the cases the victims has consumed the poison at home(83.9%).